2021
DOI: 10.1177/1038416221994312
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the career decision making of university students enrolled in STEM disciplines

Abstract: This study investigated why university students choose to major in Science, Technology, Engineering, Mathematics, and Medicine/health (STEM(M)) disciplines, and how their study and career-related confidence compares with that of their peers. The study engaged 12,576 students enrolled at Australian universities. The findings suggest that STEM(M) students’ career decision making is guided by their interest in the subject and their intentions to help people. Within the STEM(M) cohort, students in medicine and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…At the same time, it is noted that problems exist in STEM education (Garibay 2015 ; Josa and Aguado 2021 ). It is recognized that having a positive social impact entices students to enroll in STEM (Bennett et al 2021 ) and a social awareness curriculum has an impact on the engineering identity formation of high school girls Burks et al ( 2019 , p. 1). Various studies investigated the social responsibility of engineering students, seeing it as important but reporting problems (Børsen et al 2021 ; Canney and Bielefeldt 2015 ; Schiff et al 2021 ; Tomblin and Mogul 2020 ).…”
Section: Engineering Educationmentioning
confidence: 99%
“…At the same time, it is noted that problems exist in STEM education (Garibay 2015 ; Josa and Aguado 2021 ). It is recognized that having a positive social impact entices students to enroll in STEM (Bennett et al 2021 ) and a social awareness curriculum has an impact on the engineering identity formation of high school girls Burks et al ( 2019 , p. 1). Various studies investigated the social responsibility of engineering students, seeing it as important but reporting problems (Børsen et al 2021 ; Canney and Bielefeldt 2015 ; Schiff et al 2021 ; Tomblin and Mogul 2020 ).…”
Section: Engineering Educationmentioning
confidence: 99%
“…2 summarise the intersectionality of motivational factors together with the relative strength of each factor. Figure 2 shows that personal and social utility intersected with intrinsic interest but to a smaller degree than has been observed in other STEM disciplines (Bennett et al, 2020(Bennett et al, , 2021. Specifically, personal utility was influenced by perceived job availability rather than anticipated salary or job security.…”
Section: Discussion: the Importance Of Intrinsic Motivation In Itmentioning
confidence: 87%
“…Akosah-Twumasi et al, (2018) reported that personal interest was highlighted as the major factor that influenced career choice in individualistic settings, and the youth were more independent in their career decision making and that most career decisions of students are based on their personal interests. Similarly, Bennett, Knight, Bawa and Dockery (2021) reported that students' career decision making in science oriented careers is guided by their interest in the subject.…”
Section: Literature Reviewmentioning
confidence: 99%